Effect of vitamin B6 on lenses of diabetic rats - (:unkn) unknown (My University, 1998)
Vitamin B6 is essential for the metabolism of fat, carbohydrate and protein. In this study the effect of vitamin B6 on diabetes induced impairments in rat lenses was investigated. Although macroscopic examination revealed no opacification of rat lenses in any groups, uncontrolled induced diabetes caused significant decreases in lens glutathione and increases in lens protein nonenzymatic glycosylation and blood glucose. Administration of vitamin B6 did not inhibit these diabetes induced alterations significantly. SDS-polyacrylamide gel electrophoresis revealed some significant differences in some protein bands between groups.
Keywords: Animals; Male; Rats; Lens, Crystalline; Diabetes Mellitus, Experimental; Streptozocin; Pyridoxine